Fas (APO-1/CD95) in inflammatory CNS diseases: intrathecal release in bacterial meningitis - Faßbender, Klaus; Eschenfelder, Christoph C.; Hennerici, Michael G. (Journal of neuroimmunology, 1999)
Release of Fas (APO-1, CD95), a type L-membrane protein which plays a crucial role in cytokine-mediated apoptosis was investigated in bacterial meningitis, viral meningoencephalitis and multiple sclerosis in vivo. After correction for bloodbrain-CSF-disruption, significantly increased intrathecal release of Fas was demonstrated exclusively in bacterial meningitis arguing for an apoptotic cell death of granulocytes in the subarachnoidal space aimed to self-limit inflammatory host response.